The history of nature conservation between 1966 and 1970 (designation of protected areas) - Centeri, Csaba; Gyulai, Ferenc (JOURNAL OF LANDSCAPE ECOLOGY, 2011)
We continue the history of establishing nature conservation areas with the overview of the 5 years between 1966 and 1970. All data in the article belong to nature conservation areas classified by the IUCN. According to this database the most areas in number were established in Germany, almost half of those were landscape protection areas, the other half were nature reserves. Most of the areas belong to IUCN category IV (Habitat/Species Management Area: protected area managed mainly for conservation through management intervention) but 154 different national categories are represented among the designated areas. From the areas sizes the smallest areas are dominant, 46 % belong here. Only two Hungarian protected area get on the IUCN list, both representing nature conservation areas. We can state that compared to the previous five years, the number of established areas grew again between 1966 and 1970 from 1864 to 2353. From the history of nature conservation the highlight of this period is the designation of the Gombe National Park of Tanzania, the Petra National Park of Jordan, and the creation of a new name for the first Australian national park, renamed from The National Park to Royal.